(untitled) (Journal of Veterinary Medicine and Animal Production, 2022)
This study was conducted to investigate the performance of Nubian goat fed a concentrate diet supplemented with natron levels at 0- 5%. where a total of 25 Nubian goat’s kids of both sexes (7 - 9 month old) were used. They were divided into five equal groups each randomly allocated to the concentrate diet containing one of the above natron levels. The experimental period covered the three seasons; dry and wet summer, and winter. The measurements included water and food intakes, body weight changes and feed conversion ratio. The responses showed a significant increase (P<0.05) in water intake at 3% natron level and a significant reduction (P<0.05) at 5% and agin in dry summer compared to wet summer and winter. In winter the water intake increased by 3.5% than the control group (P<0.05). Progressive reduction (P<0.05) in food intake at 4 and 5% levels (20% and 27%) compred to low natron levels (0-3%) were observed. Daily feed intake in the natron supplemented groups was significantly (P<0.05) lower at all seasons than the control group. The daily feed intake during wet summer and winter increased by about 18%compared to dry season. Metabolic body weight (kg0.75) was increased insignificantly (P>0.05) at 3% Natron. During wet summer and winter it increased by 12% - 28% in the supplemented and the control groups compared to dry season. Feed conversion ratio increased significantly (P<0.05) and progressively with natron concentration 11.8% ,21.8% and 22.7% at 3%, 4% and 5% natron compared to the control group. its seasonal magnitudes were significantly (P<0.05) higher in the supplemented groups than the control one and higher ratio occurred in both groups during dry summer and winter.